Neuromuscular compatibility and its relationship to the accuracy of receiving the serve in volleyball - Assistant Lecturer. Younis Sabih Abdullah (Zien Journals, 2023)
The game of volleyball depends on many skills, including the skill of sending and receiving, which means receiving the ball from the sending player of the opposing team to prepare it for the prepared player or colleague on the field. The research study aims to identify the relationship between neuromuscular compatibility with the skill of receiving the serve in volleyball, the research problem lies in identifying the weakness in the skill of receiving the serve for the volleyball players in order to develop this skill for the volleyball players.
Keywords: Muscular Coordination; Volleyball; Skills